REVITALISASI PASAR IKAN REJOMULYO SEBAGAI DESTINASI WISATA DENGAN PENDEKATAN ARSITEKTUR PERILAKU DI KOTA SEMARANG - Crustasia Aji Westriani; Mohammad Asrori; Made Suastika (ARSITEKTURA, 2016)
The background of revitalization Rejomulyo fish market is the condition of this market was getting worse and desolate from buyers. Increasingly of tourist attraction and a lot of fish lovers community at Semarang city becomes away to resurrect this market including the physical of this building, economics, social, and bargaining culture. Therefore, Environmental Behavior Architecture was chosen to make fish market become recreational, effective, and efficient appropriate with user behavior. The purpose of this design was to make Rejomulyo fish market as a city tourist destination, with the result this market can be used again and supply the needs of society. The problem of the design is how to use both of two buildings in the market with different function in order to have competitive quality. So that created appropriate device with user’s behavior. The method used is by combining the principles of the Architecture of Conduct, regulations Indonesian Trade Minister regarding the revitalization of the market, standardize the fish market, and the real condition of the Rejomulyo fish market. The result from this design is fish market design which is hygienic place and there is a place for fish exhibition. Besides that, it also became a place for fish lover’s community to make positive activity for community and several of fish lovers. The purpose of Architecture Behavioral was to restore function Rejomulyo fish market, as well as a tourist destination Semarang comfortable, clean, effective, and efficient.